2000
DOI: 10.1038/sj.mp.4000832
|View full text |Cite
|
Sign up to set email alerts
|

Association between Novelty Seeking and the −521 C/T polymorphism in the promoter region of the DRD4 gene

Abstract: Association between the human personality trait 'Novelty Seeking' and the polymorphism of the DRD4 gene was first reported by Ebstein 1 and Benjamin 2 in 1996. This was soon followed by replication studies in various ethnic groups and by studying the role of other neurotransmitter receptor and transporter genes in the genetic determination of human temperament. More recently, several polymorphic sites of the upstream regulatory region of the DRD4 gene have been described.3 Among these the −521 C/T single nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
60
6

Year Published

2001
2001
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 27 publications
7
60
6
Order By: Relevance
“…There was no statistically significant difference between the low and high scoring groups (P = 0.91). In contrast to the report by Ronai et al, 13 homo- Table 1 The number of observed −521C/T genotypes in the high and low novely seeking groups…”
contrasting
confidence: 52%
See 3 more Smart Citations
“…There was no statistically significant difference between the low and high scoring groups (P = 0.91). In contrast to the report by Ronai et al, 13 homo- Table 1 The number of observed −521C/T genotypes in the high and low novely seeking groups…”
contrasting
confidence: 52%
“…In the case of the association described between a serotonin transporter gene polymorphism and a quantitative personality trait, neuroticism, it has been shown that the polymorphism may have an effect on trait values from the middle but not the extremes of its distribution. 18 Our study design cannot exclude a similar possibility, but we rather suggest that the association of NS with −521C/T observed by Okuyama et al 12 and Ronai et al 13 should be interpreted as a reflection of linkage disequilibrium between the studied polymorphism and the putative variant having a functional Molecular Psychiatry effect on NS scores. A dense set of polymorphisms in the DRD4 gene, its promoter as well as in other genes in the vicinity of the DRD4 gene must be studied, preferably in large, representative samples, to resolve this intriguing question.…”
Section: Lowmentioning
confidence: 88%
See 2 more Smart Citations
“…Sequence variability within the dopamine receptor D4 gene (DRD4) has been implicated in the personality trait of novelty seeking, which is related to extroversion (Benjamin et al 1996;Ebstein et al 1996). A C-to-T single nucleotide polymorphism (SNP) at position -521 of DRD4 relative to the translation start site has been associated with novelty-seeking behavior in independent studies of Japanese (Okuyama et al 2000) and Hungarians (Ronai et al 2001). With the use of a transient expression system, Okuyama et al (2000) showed that the transcriptional activity of the -521T allele of DRD4 was reduced by $40% compared with that of the -521C allele in a human retinoblastoma cell line, suggesting functional relevance of this SNP in dopaminergic neurotransmission.…”
Section: Introductionmentioning
confidence: 99%